Factor Analysis of Life Qualities of Upper Northern Undergraduate Students - Aksorndit, Phudit; Srisuk, Kiatsuda (Community and Social Development Journal, 2020)
The purposes of this research were 1) to synthesis of quality of life indicators of undergraduate students in upper northern universities and 2) to examine the Confirmatory Factor Analysis (CFA) in the quality of life of undergraduate students in the universities. The sample consisted the 1,442 undergraduate students who were studying in upper northern universities in academic year 2018. Subjects were recruited by Multi-Stage Random Samplings. The research instrument was the five point rating scales self-response questionnaire of quality of life of undergraduate students in the upper northern universities which was consists 33 items and yield for 0.963 of its validity. The data was analyzed by using an Exploratory Factory Analysis (EFA) by Equamax with Principle Component Analysis (PCA) and Confirmatory Factor Analysis. The study revealed that 1) the level of 6 factors of the quality of life of undergraduate students in those universities which were university service satisfactions, social services, social lives, study life styles, anxiety feelings and leisure activities. Each factor was described by the variance of 71.77% from 33 items and the factor loading had shown 0.573 to 0.848. Also, 2) The CFA results was fit with the empirical data with Chi-square = 10.133 (p-value = 0.256), RMSEA = 0.014, CFI = 1.000. TFL = 0.999 and SRMR = 0.007.